Potensi dan Distribusi Limbah Biomassa Pertanian sebagai Penghasil Bioenergi di Kabupaten Gunungkidul - Betti Yuniasih; Listiyani; Githa Noviana; Amir Noviyanto (AGROISTA : Jurnal Agroteknologi, 2026)
Agricultural waste has the potential to serve as an environmentally friendly source of bioenergy. This study aims to determine the potential of agricultural waste as a bioenergy source, assess the amount of bioenergy that can be generated, and identify the distribution of this energy potential within Gunungkidul Regency. This study utilizes agricultural commodity production data from the Gunungkidul Regency Agriculture Office. Biomass waste estimates were calculated using the RPR (residue-to-product ratio). Estimates of the energy produced were calculated by multiplying the estimated agricultural waste by the lower heating value (LHV) for each commodity. Data on waste utilization was collected through in-depth interviews with key figures at the Gunungkidul Regency Agriculture Office. The estimated energy values for each subdistrict were mapped using ArcGIS Pro and visualized as a color gradient. The study results indicate that the total estimated agricultural waste in Gunungkidul amounts to 1,808,807 tons per year. The primary crops contributing the highest volume of agricultural waste are cassava, corn, rice, and bananas. This agricultural waste has the potential to be processed into bioenergy in the form of bioethanol, biobriquettes, biochar, biotanol, or biogas. The districts with high-potential bioenergy from agricultural waste are Saptosari, Semin, and Ponjong, which are dominated by dryland farming of cassava, upland rice, and corn. The majority of areas in Gunungkidul Regency have moderate bioenergy potential. Agricultural waste in Gunungkidul Regency has the potential to be processed into bioenergy to foster energy self-sufficiency in each area of the regency.